Parvovirus B-19 Infection During Pregnancy - Anthony Al-Khan; Andrew Caligiuri; Joseph Apuzzio (Hindawi Limited, 2003)
The development of an acute parvovirus B-19 infection during pregnancy can cause pregnancy complications ranging from early pregnancy loss to nonimmune hydrops. There is no treatment, but preventive measures can be used to decrease perinatal mortality. The diagnosis is made on the basis of clinical suspicion and serology. If the fetus exhibits hydrops in the latter part of pregnancy, the main treatment options include either correcting the associated anemia with intrauterine blood transfusion or birth with extrauterine management. Although the serious problems associated with this virus during pregnancy are uncommon, they can be fatal. In view of this, a pregnant woman who is antibody negative should try to avoid contact with large groups of young children in order to decrease contact with potential vectors.